Theatrical Thechnology & IT Applycation circus clown Sad as sample (Al-Academy, 2024)
Means the current research to study the organization formal and its role in demonstrating aesthetic values of the publications issued by the Telecommunications Company (Asia Cell) in Iraq, where is the organization the formal need for a mission to find the concepts and dimensions of the functional and expressive and aesthetic added to the impact of the actor in achieving the goals set for the publication.The target is determined by the researcher to disclose the role of formal organization to show the aesthetic values of the publication to reach scientific results